2018
DOI: 10.1038/s41419-018-0878-1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear YAP localization as a key regulator of podocyte function

Abstract: Podocytes are crucial for the establishment of the blood-urine filtration barrier in the glomeruli of the kidney. These cells are mainly affected during glomerulopathies causing proteinuria and kidney function impairment. Ongoing podocyte injury leads to podocyte loss, finally followed by end-stage kidney disease. Podocytes display a predominant nuclear localization of YAP (Yes-associated protein), one effector protein of the Hippo pathway, which regulates the balance between proliferation, differentiation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Whether podocyte injury leads to YAP nuclear exclusion, or YAP nuclear exclusion promotes podocyte injury in vivo, is still a problem to be explored [32]. In the present study, we found accumulation of nuclear YAP in podocytes in MCD with little podocyte apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…Whether podocyte injury leads to YAP nuclear exclusion, or YAP nuclear exclusion promotes podocyte injury in vivo, is still a problem to be explored [32]. In the present study, we found accumulation of nuclear YAP in podocytes in MCD with little podocyte apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…YAP signalling is involved in the pathogenesis of cystic nephropathy and is up-regulated in fibroblasts to increase the synthesis of the extracellular matrix and to promote renal fibrosis 35 . A comparison of our data with two independent studies of transcriptional regulation in human FSGS glomeruli obtained from the Nephroseq database found that focal segmental glomerulopathy is also associated with an activation of the Hippo pathway in podocytes 36 . Further studies have found that the loss of YAP in podocytes leads to podocyte apoptosis 37,38 .…”
Section: Discussionmentioning
confidence: 58%
“…At present, most studies on YAP in podocytes suggest that the activation of YAP signalling has a protective effect on podocytes. Podocyte-specific YAP knockout can lead to the loss of foot processes, impaired renal function, and proteinuria 36,40 . In the present study, we found that the expression of desmin and snail2 significantly increased in podocytes overexpressing YAP, while expression of the podocyte cytoskeleton-associated protein, synaptopodin, significantly decreased after YAP overexpression/ Therefore, we propose that the activation of YAP signalling may have promoted podocyte re-entry into the cell cycle, leading to changes in the cytoskeleton and podocyte dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be the cause or effect of increased podocyte injury in SAGN glomeruli, and may facilitate the often encountered nephrotic-range proteinuria in SAGN. The Hippo www.nature.com/scientificreports/ pathway, also predicted to be activated in SAGN glomeruli may result in podocyte damage [27][28][29] , and contribute to the nephrotic range proteinuria. The tubulointerstitial proteome of SAGN showed significantly higher expression of TGM2, compared to IgAN, also shown by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be the cause or effect of increased podocyte injury in SAGN glomeruli, and may facilitate the often encountered nephrotic-range proteinuria in SAGN. The Hippo pathway, also predicted to be activated in SAGN glomeruli may result in podocyte damage 27 29 , and contribute to the nephrotic range proteinuria.…”
Section: Discussionmentioning
confidence: 99%